Professional Counselors' Referral Processes to Complementary Health Practitioners. Issue 3 (3rd July 2021) - Gamby, Katie; Clark, Madeline; O'Hara, Caroline; Ausloos, Clark; Delaney, Colleen; Granello, Paul
ABSTRACT: There is a growing interest in the utility of complementary health approaches (CHAs) to promote wellness and health in the United States. Research from medical, allied health, and mental health fields reflect this expanding interest; however, very little research focuses on counselors and the integration of CHAs within practice or referral of counseling clients to Complementary Health Practitioners (CHPs). The current study expanded this research using transcendental phenomenology to explore the experiences, perspectives, and processes in use by current independently licensed professional counselors referring to complementary health practitioners (CHPs). The authors discuss and explore implications of these findings.